A Study on the Improvement of Korean Journal Citation Index Service - Kim, Suntae (International Journal of Knowledge Content Development & Technology, 2021)
The KJC and KCI services operated by the National Research Foundation of Korea (NRF) need to refer to the global citation index database to set the service direction that researchers want and develop new functions. Therefore, in this study, the usability of Korea's KJC and KCI web databases was evaluated. In addition, FGI verification was performed for a group of experts on KJC and KCI improvement measures derived by academic information experts. The evaluation committee consisted of the researcher group, the society related group, the publisher (academic information distribution organization) group, and the policy-making organization group. A total of 16 experts performed usability evaluation and service improvement proposals for KJC and KCI services. As a result of usability evaluation of KJC and KCI web database using SUS measurement tool, KJC service was evaluated as 73.44, and KCI service was evaluated as good as 64.38. KJC improvement proposals were evaluated positively with 4 points or more for all improvement items, and KCI improvement proposals were positively evaluated with 3.5 points or more for all improvement items. Overall, KJC and KCI error improvements were evaluated with a score of 4 or more, showing strong affirmations. In the future, it is hoped that the improvement proposals and improvements proposed in this study will be applied to the development of KJC and KCI services, so that more quality services will be used by domestic researchers.